Perbandingan Daya Antibakteri Ekstrak dan Minyak Piper betle L. terhadap Bakteri Streptococcus mutans - Pangesti, Rizki Dwi; Cahyono, Edy; Kusumo, Ersanghono (Universitas Negeri Semarang, 2017)
Piper betle has been known as against gram positif and gram negatif bacterial including Streptococcus mutans. S. mutans is the main cause of periodental desease. The purpose of this study is to compare antibacterial power between extract and piper betle oil against S. mutans. Amoxcicilin is used as positive control and ethanol 96% for the negative one. The result show that piper betle oil is more effective than its extract against S. mutans. to know the chemical component Piper betle oil analys by GC-MS while extract screen by fitochemical. Then piper betle oil distillation fractionation was done to produce fraction I, fraction II and fraction III. Each fraction beeing tested antibacterial and analysing by GC. Second fraction is more potential to be antibacterial because it has chavicol compounds (15.039%) which is the one of the phenol group that stronger than the other phenol